The Meaning of the Film " Air Mata Mualaf " Analysis of Relevance to Riau Malay Cultural Values : A Semiotic Study - Elmustian; Dila Apri Kanisya (International Journal of Technology and Education Research, 2026)
The film Air Mata Mualaf is a work of religious drama that depicts the spiritual process of a woman in achieving her life beliefs. This research is intended to analyze the meaning contained in the film and its relationship to Riau Malay cultural values. The approach applied includes descriptive qualitative, using semiotics and content analysis. Research findings reveal that this film includes religious values, steadfastness of faith, patience, and respect for family, which is in line with the Riau Malay principle "adat bersendi syarak, syarak bersendi Kitabullah". The film plays a relevant role as an educational tool to understand the integration of culture and religion in the lives of Malay people.